Coping drinking motives, neural functional coupling during emotion processing, and alcohol use in young adults with bipolar disorder. (22nd July 2022) - Tretyak, Valeria; Kirsch, Dylan E.; Le, Vanessa; Fromme, Kim; Strakowski, Stephen M.; Lippard, Elizabeth T. C.
Abstract: Background: Rates of alcohol use disorders in individuals with bipolar disorder are 3 to 5 times greater than in the general population and exceed rates of alcohol use disorders reported in other affective and anxiety disorders. Despite this high rate of comorbidity, our understanding of the psychosocial and neural mechanisms that underlie the initiation of alcohol misuse in young adults with bipolar disorder remains limited. Prior work suggests that individuals with bipolar disorder may misuse alcohol as a coping mechanism, yet the neural correlates of coping drinking motives and associated alcohol use have not been previously investigated in this population. Methods: Forty‐eight young adults (22 bipolar disorder type I, 26 typically developing; 71% women; average age ± standard deviation = 22 ± 2 years) completed the Drinking Motives and Daily Drinking Questionnaires, and a Continuous Performance Functional magnetic resonance imaging (fMRI) Task with Emotional and Neutral Distracters. We calculated the relative difference in anterior cingulate cortex (ACC) functional coupling with the anterior insula and amygdala in response to emotional distracters compared with neutral stimuli and investigated the relations with coping drinking motives and alcohol use. Results: Across all participants, coping drinking motives were associated with greater quantity of recent alcohol use. In individuals with bipolar disorder, greater ACC‐anterior insula functional coupling was associated with greater coping drinking motives, and greater quantity and frequency of recent alcohol use. The relative difference in ACC‐anterior insula functional coupling was not associated with coping drinking motives or alcohol use in the typically developing group. Greater ACC‐anterior insula functional coupling in individuals with bipolar disorder was also associated with greater anxiety symptoms and recent perceived psychological stress. Exploratory analyses suggest that the relations between ACC‐anterior insula functional coupling and coping drinking motives may be confounded by anticonvulsant use. Conclusion: Results suggest that a difference in ACC‐anterior insula functional coupling during emotion processing may underlie alcohol use as a maladaptive coping mechanism in young adults with bipolar disorder. Abstract : Neural mechanisms of alcohol misuse initiation in individuals with bipolar disorder remain largely unknown. While the self‐medication hypothesis suggests individuals with bipolar disorder may misuse alcohol as a coping mechanism, neural correlates of coping drinking motives and associated alcohol use have not been investigated in this clinical population. Findings suggest relative differences in functional coupling between anterior limbic and paralimbic neural regions in response to negative affective stimuli may underlie alcohol consumption as a coping mechanism in young adults with bipolar disorder.